2008
DOI: 10.3113/fai.2008.0029
|View full text |Cite
|
Sign up to set email alerts
|

Plate Fixation for Crescentic Metatarsal Osteotomy in the Treatment of Hallux Valgus: An Eight-Year Followup Study

Abstract: Dorsal plate fixation of crescentic metatarsal osteotomy is a technically easier procedure. Equally good results can be achieved when compared with screw fixation methods, and the results can be maintained long-term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…When the first-second intermetatarsal angle exceeds 15 degrees it is generally believed that this degree of deformity cannot be corrected by a distal bunion procedure, but rather by some type of proximal metatarsal osteotomy or more proximal tarsometatarsal arthrodesis. 2,5,7,8,11,12,17,21,22 Whether first ray hypermobility exists as an etiological factor still remains controversial. 2,4,12,13,14 However, in severe bunion deformity wherein there is excessive metatarsus primus varus, successful correction has been well-established in the literature, going back to the original article by Lapidus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the first-second intermetatarsal angle exceeds 15 degrees it is generally believed that this degree of deformity cannot be corrected by a distal bunion procedure, but rather by some type of proximal metatarsal osteotomy or more proximal tarsometatarsal arthrodesis. 2,5,7,8,11,12,17,21,22 Whether first ray hypermobility exists as an etiological factor still remains controversial. 2,4,12,13,14 However, in severe bunion deformity wherein there is excessive metatarsus primus varus, successful correction has been well-established in the literature, going back to the original article by Lapidus.…”
Section: Discussionmentioning
confidence: 99%
“…2,3,7,11,12,14,21,24 Several techniques have been used for fixation including Kirschner wires, partially threaded cancellous screws, Steinman pins, 3.5-mm or 4.5-mm cortical screws, and 1/4 tubular plates or so-called "H-plates." 5,20 Outcome studies have demonstrated a high satisfaction rate with this procedure, but the reported incidence of nonunion or malunion has ranged from 5% to 15%. 8 Sangeorzan and Hansen reported a revision rate of 13% for mal-or nonunion following Lapidus bunion surgery.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 4607 studies were excluded by examining their titles and/or abstracts, and a further 143 studies were excluded after full-text review. This left 17 eligible studies 1,3-6,9,11-14,16-20,22-24,27,30,31,33,34,36-39 that reported on 18 data sets, representing a total of 2105 feet (Table 1, Figure 1). Of the 18 data sets, 9 assessed outcomes of Chevron osteotomies, 3 assessed Mitchell osteotomies, 2 assessed Bösch osteotomies, and 4 assessed “other” osteotomies: 1 Hohmann osteotomy, 1 percutaneous distal retrocapital osteotomy, 1 minimally invasive technique, and 1 minimally invasive intramedullary nail device.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding postoperative treatment, most authors allow full weightbearing in a stiff‐soled shoe or cast during the first two weeks after surgery, while some only allow heel weightbearing [4, 7, 8, 11]. Early ambulation with full weightbearing reduces the risk of deep vein thrombosis and prevents muscular atrophy.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past 10 years, some surgeons have increasingly used locking plates instead of a single screw for stabilisation of the osteotomy with the assumption of better postoperative stability and preserved length of the first metatarsal. In addition, fixation with a plate has been described as technically less challenging [3][4][5][6][7][8]. However, we prefer a proximal openwedge chevron-like osteotomy combined with medial bone impaction and single screw stabilisation [3].…”
Section: Introductionmentioning
confidence: 99%